Thunderstorm forecast technique for Noi Bai Airport - Tien, Tran Tan; Linh, Nguyen Khanh; Thanh, Cong; Huy, Le Quoc; Hoang Dzung, Do Thi (VNU Journal of Science: Earth and Environmental Sciences, 2008)
Abstract